If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 1) = 9(2x + -1) Reorder the terms: 3(1 + 4x) = 9(2x + -1) (1 * 3 + 4x * 3) = 9(2x + -1) (3 + 12x) = 9(2x + -1) Reorder the terms: 3 + 12x = 9(-1 + 2x) 3 + 12x = (-1 * 9 + 2x * 9) 3 + 12x = (-9 + 18x) Solving 3 + 12x = -9 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 3 + 12x + -18x = -9 + 18x + -18x Combine like terms: 12x + -18x = -6x 3 + -6x = -9 + 18x + -18x Combine like terms: 18x + -18x = 0 3 + -6x = -9 + 0 3 + -6x = -9 Add '-3' to each side of the equation. 3 + -3 + -6x = -9 + -3 Combine like terms: 3 + -3 = 0 0 + -6x = -9 + -3 -6x = -9 + -3 Combine like terms: -9 + -3 = -12 -6x = -12 Divide each side by '-6'. x = 2 Simplifying x = 2
| -6n(1+10n)= | | 0=11x-3x^2-10 | | -43=6b+8 | | 125m-100m+38800=40200-175m | | -6(x+3)-12=17+7 | | 1.39=ln(y) | | 6a^2-a-15= | | 2y+1y+15=22 | | 6x=16-x^2 | | 1/3(3.14)(3.5^2)8 | | 6y+2-7y= | | 18-9b=-b^2 | | -14=2(u+8)-7u | | -11u--6u-2u-8=20 | | f(x)=12x-x^3 | | 6.9x-2.1=25.5 | | y-17/19=-719 | | 3k-1-6k=4k+8-9k | | 7x+26=5x+56 | | 2m^2=-7m | | -14=3(x-8)-8x | | C^2-13c+40= | | 8(w+4)-5w=20 | | -12x+5y=60 | | 4-.4x=.2x-8 | | 3x(2x+4)=6(5x+2) | | 8w+3-10w= | | 2w-11w=-12 | | 7.9=2n-5 | | y+y+x+39=180 | | X+X+10=56 | | 25a^3+20a^2+3a= |